Musical and social factors affecting attention regulation of children in band playing and mobile music making - Kolomainen, Sara (2017)
This study focuses on attention and hyperactivity regulation of children in band playing and mobile music making. The study aims at finding the musical and social elements that help children to regulate their attention, and lead to positive social interaction. Within the mobile music making, stand-alone playing and pair work scenarios are analysed. Within the band playing, instructed and improvised playing are compared.